Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Jurusan Akuntansi Terhadap Pemilihan Berkarir Dibidang Perpajakan Dengan Religiusitas Sebagai Variabel Moderasi (Studi Kasus Pada Universitas Negeri Di Pekanbaru) - Nanda Suryadi; Arie Yusnelly; Chika Chika (JURNAL PUNDI, 2021)
This study aims to determine the factors that influence the interest of students in the accounting department to have a career in the field of taxation. This type of research is quantitative. The population and sample in this study were students of the Accounting Department, Sultan Syarif Kasim State Islamic University, Riau and Riau University, Class of 2016. The data collection technique used a questionnaire. Data were analyzed using PLS (Partial Least Square) analysis technique through SmartPLS software. The results showed that the variables of perception, professional recognition, and labor market considerations had a positive effect on student interest. While the variables of motivation, financial rewards, and religiosity have no effect on student interest.